MYB134-RNAi poplar plants show reduced tannin synthesis in leaves but not roots, and increased susceptibility to oxidative stress. (10th August 2020) - Gourlay, Geraldine; Ma, Dawei; Schmidt, Axel; Constabel, C Peter
Abstract: The importance of the poplar MYB134 gene in controlling condensed tannin (CT) biosynthesis was tested by suppressing its expression using RNA interference (RNAi). MYB134-RNAi plants grew normally but showed reduced accumulation of stress-induced CTs in leaves. RNA-seq analysis indicated that flavonoid- and CT-related genes, as well as additional CT regulators, were strongly and specifically down-regulated by MYB134 suppression. This confirmed that the primary MYB134 target is the leaf flavonoid and CT pathway. Root CT accumulation was not impacted by MYB suppression, suggesting that additional CT regulators are active in roots and emphasizing the complexity of the regulation of CTs in poplar. To test the effect of CT down-regulation on oxidative stress resistance, leaves of MYB134-RNAi and control plants were exposed to the reactive oxygen species generator methyl viologen. MYB134-RNAi leaves sustained significantly more photosystem II damage, as seen in reduced chlorophyll fluorescence, compared with wild-type leaves. MYB134-RNAi leaves also contained more hydrogen peroxide, a reactive oxygen species, compared with the wild type. Our data thus corroborate the hypothesis that CT can act as an antioxidant in vivo and protect against oxidative stress. Overall, MYB134 was shown to be a central player in the regulation of CT synthesis in leaves. Abstract : RNAi suppression of MYB134 in poplar uncovers organ specificity in the control of condensed tannin biosynthesis, and demonstrates a function of these compounds in defense against oxidative stress.